1973
DOI: 10.1139/f73-279
|View full text |Cite
|
Sign up to set email alerts
|

Use of Plastein Reaction in Recovering Protein from Fish Waste

Abstract: A high quality proteinaceous product is recoverable in 35% yield from fish waste by a process of peptic hydrolysis followed by a pepsin-catalyzed recombination of soluble peptides to form plastein. Hydrolysis is at pH 2.0 and 37 C for 6 hr. Soluble peptides are then separated from insoluble residue, adjusted to pH 4.5, concentrated at 45 C to 30% protein solids, and incubated for 24 hr at 37 C with additional pepsin. The insoluble plastein formed during incubation is filtered, washed, and dried. In a pilot exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The results of this study compare favorably with those of Onoue and Riddle (1973) who found a 35% plastein 'yield using pepsin as the synthesis enzyme at pH 5 and peptic hydrolysates of whole fish waste as the substrate. The yields were based on percent plastein recovery using 50% ethanol as the precipitating agent.…”
Section: Yields Of Enzymatically Induced Plasteinsupporting
confidence: 79%
“…The results of this study compare favorably with those of Onoue and Riddle (1973) who found a 35% plastein 'yield using pepsin as the synthesis enzyme at pH 5 and peptic hydrolysates of whole fish waste as the substrate. The yields were based on percent plastein recovery using 50% ethanol as the precipitating agent.…”
Section: Yields Of Enzymatically Induced Plasteinsupporting
confidence: 79%
“…Several protein-containing agricultural and food materials have been utilized as substrates for plastein formation including soybean, plant leave proteins, zein, wheat, egg albumin, milk, corn, mycoprotein, squid, fish and fish silage [4], [11], [24], [30], [31], [34], [36], [39], [52].…”
Section: Plastein Productionmentioning
confidence: 99%
“…In general, proteinogenic amino acids have the potential to form plastein under optimum conditions but those with hydrophobic side chains are more likely to be easily incorporated into plastein [3] , [12] . Several protein-containing agricultural and food materials have been utilized as substrates for plastein formation including soybean, plant leave proteins, zein, wheat, egg albumin, milk, corn, mycoprotein, squid, fish and fish silage [4] , [11] , [24] , [30] , [31] , [34] , [36] , [39] , [52] .…”
Section: Plastein Productionmentioning
confidence: 99%
“…
Attempts have been made earlier to recover proteins from fishery wastes by their ensilation and subjecting the resulting silage to the plastein reaction (Onoue and Riddle 1973; Ooshiro et a1 1981), but the ensilation conditions were not fully investigated and external proteinases were also used for hydrolysis in these experiments. This report details the ensilation conditions and factors affecting plastein synthesis (PS) from fish viscera silage.

To make the silage, stored frozen rainbow trout viscera (Raghunath and McCurdy 1990) (Onchorhynchus mykiss) were thawed, diluted with water (1 :1) and mixed slowly with formic acid (30 g kg-l), and the pH was adjusted to 2.0 with 6 M H,SO, unless otherwise mentioned.

…”
mentioning
confidence: 99%